2016
DOI: 10.1167/iovs.16-19529
|View full text |Cite
|
Sign up to set email alerts
|

Tetramethylpyrazine Attenuates Transdifferentiation of TGF-β2–Treated Human Tenon's Fibroblasts

Abstract: Citation: Cai X, Yang Y, Chen P, et al. Tetramethylpyrazine attenuates transdifferentiation of TGF-b2-treated human Tenon's fibroblasts. Invest Ophthalmol Vis Sci. 2016;57:4740-4748. DOI:10.1167/iovs.16-19529 PURPOSE. To investigate the pharmacologic effect of tetramethylpyrazine (TMP) on human Tenon's fibroblasts (HTFs), the cells implicated in scarring after filtration surgery. METHODS.Transforming growth factor-b2 (TGF-b2) was used to stimulate a fibrotic phenotype in primary HTFs, and the influence of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
(56 reference statements)
1
8
0
Order By: Relevance
“…TGF-β1 has been shown to stimulate myofibroblast differentiation, extracellular matrix synthesis, or fibrosis in corneal-fibroblast 25 conjunctival fibroblasts 26 , 27 , human retinal pigment epithelial cell 28 , and orbital fibroblasts 29 . TGF-β2 has also been reported to induce expression of extracellular matrix and/or fibrosis in cultured astrocytes of the human optic nerve head 30 , human Tenon’s fibroblasts 31 , and trabecular meshwork 32 . Current study revealed TGF-β1, but not TGF-β2, could induce CTGF, fibronectin, and α-SMA in Graves’ orbital fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β1 has been shown to stimulate myofibroblast differentiation, extracellular matrix synthesis, or fibrosis in corneal-fibroblast 25 conjunctival fibroblasts 26 , 27 , human retinal pigment epithelial cell 28 , and orbital fibroblasts 29 . TGF-β2 has also been reported to induce expression of extracellular matrix and/or fibrosis in cultured astrocytes of the human optic nerve head 30 , human Tenon’s fibroblasts 31 , and trabecular meshwork 32 . Current study revealed TGF-β1, but not TGF-β2, could induce CTGF, fibronectin, and α-SMA in Graves’ orbital fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Primary cultures of HTFs were established as previously described [ 28 , 29 ]. Briefly, Tenon’s capsule samples were cut into small pieces and cultured in Dulbecco’s modified Eagle’s medium/nutrient mixture F-12 (DMEM/F12, Solarbio) containing 10% FBS (Gibco, Gaithersburg, MD) and 1% penicillin/streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…Small biopsied Tenon's capsule specimens were isolated from five patients when they underwent a strabismus surgery. After being washed, the tissues were cultured for preparation of HTFs, as described previously 11 . The HTFs were cultivated in Dulbecco's Modified Eagle's medium (DMEM) containing 10% of fetal bovine serum (FBS) and the cells were passaged every 3-5 days.…”
Section: Primary Cell Culture and Quality Controlmentioning
confidence: 99%